Health Education on Operative Cataract Care: A Scoping Review - Prima Widya Ridwanti, Luh Putu; Swarjana, I Ketut; Kusuma Negara, I Gusti Ngurah Made; Yudara Sandra Putra, Putu Gde (Jurnal Epidemiologi Kesehatan Indonesia, 2025)
Cataract is the leading cause of blindness worldwide, requiring surgery and appropriate patient and family education to ensure proper operative care. This literature review aimed to identify health education on operative cataract care. The type of this study is a scoping review using the PubMed database, ScienceDirect, and other sources that were published in the last 10 years (2015-2024). The PICO model (P: patients and families; I: audiovisual, booklets, leaflets, and others; C: standard care or education; O: knowledge and skills in cataract operative care) was used. The keywords used to search for articles are cataract surgery AND video OR audiovisual OR booklets OR leaflets. The initial search results for articles, until included, are described in the PRISMA diagram. The results of the article search from PubMed obtained 406 articles, and from ScienceDirect 258 articles; other sources 15 articles, so the total number of articles obtained was 679 articles. Records screened 664 articles, reports sought for retrieval 247 articles, and reports assessed for eligibility 60 articles. For articles from sources, the report assessed for eligibility was three articles. Furthermore, the total studies included in the review were 15 articles. The educational interventions (video-based, telephone, social media, and web) were effective in increasing patient knowledge. However, their comparative effectiveness is unknown. Keywords: Cataract Operative Care, Health Education, Knowledge and Skills, Patient and Family